Ranking All DEA-Efficient DMUs Based on Cross Efficiency and Analytic Hierarchy Process Methods - Akbarian, Dariush (Journal of Optimization, 2015)
The aim of this paper is to present an original approach for ranking of DEA-efficientDMUs based on the cross efficiency and analytic hierarchy process (AHP) methods. Theapproach includes two basic stages. In the first stage using DEA models the cross efficiencyvalue of each DEA-efficiency DMU is specified. In the second stage, the pairwise comparisonmatrix generated in the first stage is utilized to rank scale of the units via the one-stepprocess of AHP. The advantage of this proposed method is its capability of ranking extremeand nonextreme DEA-efficient DMUs. The numerical examples are presented in this paperand we compare our approach with some other approaches.